2016
DOI: 10.20525/ijrbs.v5i4.551
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Brands on Consumer Buying Behavior

Abstract: The aim of this research is to understand the factors behind smartphone purchase decisions of consumers. Nowadays companies make use of various strategies in order to attract new customers, retain existing customers and differentiate their products from those of their competitors. Perhaps, the most important and effective strategy to influence consumer behavior in the product selection is emphasizing the “brand name” of the products. Our aim in this paper is to investigate how smartphone brands can influence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 38 publications
8
31
0
5
Order By: Relevance
“…Affecting Smartphone Consumer Satisfaction of Generation-Y shows the results that product quality has a positive and significant effect on consumer satisfaction. In another study conducted by Akkucuk and Esmaelli (2016) with the title The Impact of Brands on Consumer Buying Behavior: An Empirical Study on Smartphone Buyers states that product quality is a very significant influence on consumer satisfaction.…”
Section: Shabrin Et Al (2017) With His Research Entitled Factorsmentioning
confidence: 99%
“…Affecting Smartphone Consumer Satisfaction of Generation-Y shows the results that product quality has a positive and significant effect on consumer satisfaction. In another study conducted by Akkucuk and Esmaelli (2016) with the title The Impact of Brands on Consumer Buying Behavior: An Empirical Study on Smartphone Buyers states that product quality is a very significant influence on consumer satisfaction.…”
Section: Shabrin Et Al (2017) With His Research Entitled Factorsmentioning
confidence: 99%
“…The emergence of Internet-based social media has made it possible for people to communicate online, and this new world changed rules of old-style offline socialization (Gencer, 2015). Since most online transactions are now carried out via mobile phones (smart phones), the driving forces behind consumer behavior in this area need further investigation (Akkucuk & Esmaeili, 2016). The attractiveness and power of e-commerce lies in its impact on re-shaping traditional value chains in different industries and it represents a fundamental transformation of traditional business models (Chen & Tan, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unique post and related content can engage consumers in a personal way and affect people on an emotional level. Previous study has indicated that social media has significant impact on loyalty (Laroche, 2013) and loyalty influence significantly on consumer buying decision (Akkucuk, 2016).…”
Section: Introductionmentioning
confidence: 98%